III Biennial of Havana : Cuba, 1989. - Lalit Kala Akademi, New Delhi (New Delhi : Lalit Kala Akademi, 1989)
Bhaskaran, R.B. ; Chandrashekar C. ; Chillar, J.K. ; Choyal, P.N. ; Choyal, Shail ; Das, Sunil ; Dengle, Diwakar ; Dhumal, RIni ; Dutta Ray, Shyamal ; Kumar, Anil ; Mistry, C.D. ; Reddy, D.LN. ; Sthapathy, Vidyasanker S.G.
III Biennial of Havana : Cuba, Lalit Kala Akademi, New Delhi, 1989
boek